2022
DOI: 10.1159/000525007
|View full text |Cite
|
Sign up to set email alerts
|

Undisclosed Sexual Risk Exposures: Results of a Nationwide Compliance Study among Whole Blood Donors in Germany

Abstract: <b><i>Background:</i></b> Undisclosed sexual infection risks are the main reasons for transfusion transmissible infections in German blood donors that have qualified for donation by donor health interviews and questionnaires. Until now, data about compliance with deferral criteria were only available from post-donation interviews with infected donors, and information about the proportion of donors which did not disclose (sexual) risks at the donor health questionnaire was not available.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The age-dependent non-compliance in our study is consistent with the observed higher non-disclosure of sexual risk exposures in donors younger than 35 years [3]. However, male and female donors differ in their compliance to sexual and non-sexual deferral criteria.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The age-dependent non-compliance in our study is consistent with the observed higher non-disclosure of sexual risk exposures in donors younger than 35 years [3]. However, male and female donors differ in their compliance to sexual and non-sexual deferral criteria.…”
Section: Discussionsupporting
confidence: 90%
“…However, male and female donors differ in their compliance to sexual and non‐sexual deferral criteria. Non‐disclosure of sexual risks is more pronounced in male donors [3], whereas non‐sexual risk exposures were less frequently indicated by women. Therefore, gender‐specific donor education might help to reduce non‐disclosure of risk exposures that are relevant for donor selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current systematic review focuses on observational studies concerning TTI risk in MSM blood donors and after easing the MSM deferral. When informing policy-making, other sources of currently available information should be used as well, including findings on compliance and donor comfort when using alternative questions [11,53,54], modelling studies [48][49][50] and surveillance reports [55,56]. In addition, other criteria, including the feasibility and cost-effectiveness of alternative deferral periods, should be further examined and considered when making decisions.…”
Section: Discussionmentioning
confidence: 99%